Factors Associated with Adolescent Sexual Behavior at Public Health Centers (Puskesmas): A Cross-Sectional Study - Egatri Lidianovita Pakilaaran (Universitas STRADA Indonesia, 2026)
Adolescent sexual behavior is a major public health concern due to its association with sexually transmitted infections, unintended pregnancies, and psychosocial problems. This study aimed to analyze factors associated with sexual behavior among adolescents at public health centers (Puskesmas). A cross-sectional design was conducted involving 150 adolescents aged 15–19 years selected using simple random sampling. Data were collected using structured questionnaires covering knowledge of reproductive health, attitudes toward premarital sex, peer influence, media exposure, and sexual behavior. Data analysis was performed using chi-square tests and logistic regression. The results showed that 38.7% of respondents had risky sexual behavior. Knowledge (p=0.002), attitudes (p=0.001), peer influence (p=0.000), and media exposure (p=0.004) were significantly associated with adolescent sexual behavior. Peer influence was the most dominant factor (OR=3.45). In conclusion, adolescent sexual behavior is influenced by individual and social factors. Strengthening reproductive health education and peer-based interventions at Puskesmas is recommended.